ACTIVATION OF STUDENT MENTAL ACTIVITY IN PRACTICAL CLASSES IN A FOREIGN LANGUAGE (Pedagogy of Higher and Secondary Education, 2003)
Taking into account the age peculiarities of the 4-th year students the exercises providing the development of verbal-logical thinking memory training and the improvement of professional creative thinking have been created.